Development of mechanical prosthetic hand system for BCI application - Abu Osman, Noor Azuan; Abu Yahud, S.; Goh, S.Y. (2008)
The study is to develop a prosthetic hand that can be controlled by Brain-Computer Interface (BCI). The proposed prosthetic hand consists of palm and 5 fingers. The hand was designed to perform the 4 predetermined essential tasks in BCI applications; cylindrical grasp, key pinch, pulp to pulp pinch and tripod pinch. The phalanges of the finger was modeled as three link open chain joined at the metacarpal joint (MCP), proximal joint (PIP) and distal joint (DIP). Each segment denote as phalanx was made from two parallel aluminum plates and connected to the other segment using a bolted spacer acting as hinge joint. Length of each segment was made such that it will form an equiangular motion path during trajectory. Each joint is actuated by its individual actuator. Two mechanisms were proposed in this study. The first mechanism is the tendon drive; used terelyne string to pull each segment to flexion. The second mechanism is a spring return; a stored resistive force in torsion spring will kick the segment to its initial position. The hand was equipped with potentiometers and pressure sensors for control purposes. The prototype was tested with BCI system, in order to meet its initial objective and additional tests were carried out to evaluate its performance. An experiment to test the performance of the prosthetic hand was carried out successfully. Strength of each tendon was measured using a proof ring method and motion images were captured using video camera and analyzed using Peak Motus Performance 2000 Motion Analysis software.